Intelligent Surveillance System for IoT Application - Sangeetha E, Devagiri Alekhya, Vennapusa Sahithya, Terala Sai Harthik, Rajesh S M, (International Journal of Advanced Science and Technology, 2020)
Now a days Surveillance System and Internet of Thing (IoT) is the emerging technology. In this project a surveillance system has be implemented using a single board computer i.e. Raspberry Pi 4 to reduce man power for security aspects. A local database of the authorized person is created which has the images of all individuals allowed to access that security area. Camera will act as the computer vision which is in surveillance mode, once the motion is detected the video recording triggers which will take the image of the person and compare the image with local database. If the person image matches then the intruder is authorized else the intruder is unauthorized hence buzzer will on and the surveillance system send SMS and Email notification containing the image of the unauthorized person as attachment with date and time, when image is captured and is triggered by raspberry pi to owner and security guard.